United Nations Decade of Ocean Science for Sustainable Development (2021-2030): From innovation of ocean science to science-based ocean governance - Guan, Song; Qu, Fangyuan; Qiao, Fangli (Frontiers in Marine Science, 2023)
United Nations Decade of Ocean Science for Sustainable Development (2021-2030) (hereafter the Ocean Decade) was officially launched at the beginning of 2021. This global initiative, which is designed and coordinated by the United Nations, aims to improve ocean governance at global, regional and national levels including supporting United Nations entities to fulfil their ocean-related mandates by means of providing innovative science-based solutions. Therefore, it will be of great significance to analyze and then have a deep and comprehensive understanding of the Ocean Decade with focus on its immediate and long-term influences to ocean governance. This paper introduces the background, Implementation Plan and recent main progress of the Ocean Decade, as well as China’s contributions to the Ocean Decade and its national plan of implementing the Ocean Decade. Besides, this paper analyzes, evaluates and predicts what influences the Ocean Decade will bring to ocean governance at different levels in the future. Finally, this paper provides some suggestions for scientists, legal scholars and policy-makers on how to jointly build stronger science-policy interfaces under the framework of the Ocean Decade.